Taken hostage [videorecording (DVD)] - Stone, Robert, 1958- (WGBH, PBS, 2022)
The Iran hostage crisis involved 52 American diplomats, Marines, and civilians held by force at the American Embassy in Tehran on November 4, 1979. Unfolding like a political thriller, see how hostages' personal lives were torn apart and scrutinized through publicity, correspondents risked their lives to discover the truth about Iran, and military forces attempted to rescue the victims.